Las coaliciones de partidos: ¿un nuevo escenario para el sistema partidista chileno? - Huneeus Madge, Carlos (Política. Revista de Ciencia Política, 2005)
The presidential and congressional elections of 2005 will allow the continuity of the Concertación por la Democracia with a fourth government. Governance conditions are given by a government coalition majority in both chambers, for the first time since 1990. However, the shift of the coalition internal force from PDC towards the PS/PPD/PRSD bloc with the help of the binominal system creates a complicated situation. This will force the government into a policy of agreements, with a possibility of obtaining support from opposition in Congress, especially from National Renewal. This, especially if the objective isto insist on the decision to grow towards the Center if the aim is to diminish UDI’s hegemony within the Right. In sum, the fourth democratic government may result in a transition towards a new stage in politics after Pinochet.